Implementasi Program Kota Layak Anak Di Dinas Pemberdayaan Perempuan Dan Perlindungan Anak Kota Bengkulu - Syafitri, Tania; Hakim, Kahar; Nursanty (Faculty of Social and Political Sciences Universitas Prof Dr Hazairin, SH, 2024)
This research adopts the policy implementation theory developed by Riant Nugroho (2017) and analyzed using Van Metter and Van Horn theory, focusing on the implementation stages, and referring to Bengkulu City Regional Regulation Number 11 of 2021 concerning the Implementation of a Child Decent City. The aspects that are the focus of the research involve socialization of KLA programs, monitoring the implementation of KLA, coordinating the mobilization of fund resources and KLA facilities and infrastructure, as well as the implementation of programs related to child protection issues, namely children's forums. The research method applied is descriptive qualitative, To strengthen the argument, the author collects data through observation, interviews, and documentation. The results showed that the implementation of the Child Decent City Program at the Women's Empowerment and Child Protection Office of Bengkulu City has not reached an optimal level. These obstacles are Regional Apparatus Organizations (OPD) which are still difficult .